2005
DOI: 10.1016/j.jms.2005.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Self-broadened line parameters for water vapour in the spectral region 5000–5600cm−1

Abstract: The self-broadening coefficients and intensities of approximately 460 of the strongest water vapour lines (intensity S ≥ 1.5x10-23 cm molec compilation, which revealed marked systematic differences in the self-broadening coefficients (up to 20%) and in the line intensities (up to 5%). The possible reasons for these deviations are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Spectra under various conditions of path-length, pressure and in presence of air have been recorded to determine the positions, the intensities, the self-and air-broadening coefficients and the pressure-induced shifts of about 10,400 lines belonging to the four isotopologues Intensities have been measured for all observed lines, more than 30% of them being determined experimentally for the first time. For common sets of measurements, our intensity data agrees well on average with previous experimental works [21,22,[25][26][27]60,61] particularly for strong and medium lines. A detailed comparison with literature results has been done including the examination of the averaged A and R statistical criteria: the linear regression coefficient (A) and the median of intensity ratios distribution (R) that provide information on absolute intensity calibrations among various data sources.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Spectra under various conditions of path-length, pressure and in presence of air have been recorded to determine the positions, the intensities, the self-and air-broadening coefficients and the pressure-induced shifts of about 10,400 lines belonging to the four isotopologues Intensities have been measured for all observed lines, more than 30% of them being determined experimentally for the first time. For common sets of measurements, our intensity data agrees well on average with previous experimental works [21,22,[25][26][27]60,61] particularly for strong and medium lines. A detailed comparison with literature results has been done including the examination of the averaged A and R statistical criteria: the linear regression coefficient (A) and the median of intensity ratios distribution (R) that provide information on absolute intensity calibrations among various data sources.…”
Section: Resultssupporting
confidence: 89%
“…4(a)-(d): the weakest lines are missing in panels (a) and (b) [22,60]; strong lines are missing in panels (b) and (c) [21,60]; and panel (d) only contains strong lines [61]. The number of previously measured intensities in this wave number range compared to our data (in %) is given in the second column of Table 10.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…In the 5000–5600 cm −1 region Ptashnik et al [2005] reported that HITRAN‐2004 systematically overestimates the self‐broadened half widths by up to 20% and intensities by up to 5%. Therefore in this region the measured intensities and self‐broadened half widths derived by Ptashnik et al are used in preference to those given in HITRAN‐2004.…”
Section: Resultsmentioning
confidence: 98%